PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR IPS SISWA DI SEKOLAH DASAR - Sari, Siska Winda; Miaz, Yalvema; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine whether there is a significant effect of using the Jigsaw cooperative model on student learning outcomes in social studies learning in class V SDN 13 Cingkariang. This type of research is a quasi-experimental study with non equivalent control group design. The population in this study was 204 people, sampling data was taken by purposive sampling technique, and obtained as many as 50 research samples. Based on the results of the research that has been done, the average posttest of the experimental class 85.6 and control class 65.6 is obtained with a difference of 20 numbers, then the results of the t test obtained t count> t table which is 8.06> from 1.67722 with α = 0.05 means that Ho is rejected, so Ha is accepted, namely there is a significant effect of using the Jigsaw cooperative model on student learning outcomes in social studies learning in class V SDN 13 Cingkariang Banuhampu District, Agam Regency.